2011
DOI: 10.1242/jeb.052100
|View full text |Cite
|
Sign up to set email alerts
|

Significant dissociation of expression patterns of the basic helix–loop–helix transcription factors Dec1 and Dec2 in rat kidney

Abstract: SUMMARYDec1 and Dec2 are regulators of the mammalian molecular clock that show robust circadian rhythms in the suprachiasmatic nucleus and various peripheral tissues. Although the expression of Dec1 and Dec2 is altered by multiple stimuli in different organs, their transcriptional regulatory mechanisms have not been fully elucidated for the kidney. In the present study, we describe for the first time significant dissociation of expression patterns with arrhythmic expression of Dec1 and rhythmic expression of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…We found that DRF can induce a bimodal temporal pattern of corticosterone secretion in normal rats, with the first peak appearing at the beginning of the day, depending on the feeding time, and the second one appearing just before the LD transition controlled by the SCN clock (43), which was in good agreement with previous observations in normal mice under the DRF condition (22). These observations suggest the secretion of glucocorticoid hormone is under the control of both internal SCN and external feeding schedule in normal rodents.…”
Section: Discussionmentioning
confidence: 79%
“…We found that DRF can induce a bimodal temporal pattern of corticosterone secretion in normal rats, with the first peak appearing at the beginning of the day, depending on the feeding time, and the second one appearing just before the LD transition controlled by the SCN clock (43), which was in good agreement with previous observations in normal mice under the DRF condition (22). These observations suggest the secretion of glucocorticoid hormone is under the control of both internal SCN and external feeding schedule in normal rodents.…”
Section: Discussionmentioning
confidence: 79%
“…Gene expression of both Dec1 and Dec2 exhibits a circadian pattern of expression in the rat heart while only Dec2 shows a comparable rhythm in the kidney (Wu et al 2011). Since rats are nocturnal, they normally eat at night.…”
Section: The Kidney Clockmentioning
confidence: 99%
“…DEC2 mRNA is known to show a rhythmic expression in SCN, kidneys, liver, muscles, sarcoma cells and hepatocellular carcinoma HepG2 cells (3,21,25,38,39). However, there are no studies available on the rhythmic expression of DEC2 protein.…”
Section: Discussionmentioning
confidence: 99%